PENGARUH SUMBER AIR PENYIRAMAN DAN FREKUENSI PENYEMPROTAN INSEKTISIDA TERHADAP PERTUMBUHAN DAN KANDUNGAN TIMBAL (Pb) PADA TANAMAN SELADA - Etik Puji Handayani; Rakhmiati Rakhmiati; Yatmin Yatmin (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2008)
Water management and technology of protection insectiside could be changes availability heavy metal in soil and plant. The objective of this research was to study the effect of water source to spray vegetables and frequency sprayer insecticide on the growth and Pb contain in vegetable. The experimental design was factorial in randomized completely block design with three replications. The result showed the effect of water source to spray vegetables and frequency insecticide spray not significant on the growth vegetables, but significant on Pb contain in vegetables. The maximum Pb (7,97 ppm) in sludge from household and twice insecticide spray.Keywords: Water source, frequency insecticide, Heavy metal Pb, vegetable.